Painful erections secondary to rare epithelioid hemangioma of the penis - Barber, Evan; Domes, Trustin (Canadian Urological Association Journal, 2014)
Epithelioid hemangioma is a rare benign vascular tumour that atypically involves the penis and usually presents as a painful nodule. A 35-year-old man presented with a 5-month history of painful erections without a clinically apparent lesion or deformity. Magnetic resonance imaging (MRI) with pharmacologically induced erection demonstrated a 1.3-cm nodular lesion deep to the skin at the base of his penis. Following local excision of the lesion, which was diagnosed as an epithelioid hemangioma, the patient was symptom free. This case demonstrates a rare etiology of painful erections with a unique presentation. To the authors’ knowledge, it is also the first report of MRI with intracavernosal injection of trimix to assess for a specific cause of painful erections.